CYCLICAL METHODS OF SORTING THE INDEX ELEMENTS DATASETS - I. P. Kadiev; P. A. Kadiev (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In work cyclic methods of index sorting of data files, at the heart of which shift of elements for the purpose of receiving the configurations possessing certain properties are considered.